Business Intelligence System and innovative work behaviour in UAE SME and the mediating roles of knowledge sharing and SME innovation - Alderei, Saif Khalifa Mohamed Mubarak (2026)
In today’s increasingly dynamic and competitive business environment, Business Intelligence Sys- tems (BIS) serve as critical enablers of innovation and data-driven decision-making, especially for Small and Medium Enterprises (SMEs). In the United Arab Emirates (UAE), SMEs account for ap- proximately 94% of all registered businesses, contribute over 60% to the non-oil GDP, and employ nearly 86% of the private sector workforce. Despite their strategic economic role, many UAE SMEs struggle to foster sustainable innovation, often due to limited adoption of BIS and underdeveloped knowledge-sharing cultures. This study investigates the impact of BIS on Innovative Work Behavior (IWB) and explores the mediating roles of Knowledge Sharing (KS) and SMEs Innovation (SMEI). Grounded in the Technology-Organization-Environment (TOE) framework and using a cross-sec- tional quantitative design, data were collected from 386 SME owners, managers, and shareholders across the UAE who have adopted or are in the process of adopting BIS. Partial Least Squares Struc- tural Equation Modeling (PLS-SEM) was applied using SmartPLS 4 to analyze the relationships among variables. The findings confirmed that several BIS components specifically data integration, information access quality, information content quality, use of information in business processes, and analytical decision-making culture significantly enhance IWB. However, analytical capabilities alone did not demonstrate a significant direct effect on IWB. Knowledge sharing was not found to directly influence IWB significantly; nonetheless, it exhibited a statistically significant mediating effect in the relationships between analytical capabilities, use of information in business processes, and analytical decision-making culture with IWB. Similarly, SME innovation significantly mediated the relationships between analytical capabilities and information content quality with IWB. These findings suggest that while knowledge sharing and SME innovation may not universally mediate all BIS components, they play pivotal roles in shaping how specific BIS functions influence innovative behaviors. This study makes a notable theoretical contribution by refining the TOE framework through the dual mediation model involving KS and SMEI. It also provides practical implications for SME leaders and policymakers, urging them to prioritize BIS implementation alongside the cul- tivation of innovation-friendly and knowledge-sharing cultures. Strengthening these organizational capabilities can substantially enhance individual-level innovation, contributing to overall SME com- petitiveness and economic sustainability in the UAE.